2020
DOI: 10.1097/mcp.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in patients with interstitial lung disease

Abstract: Purpose of reviewThe incidence of age-related diseases such as interstitial lung disease (ILD) is rising, and the importance of multimorbidity and accumulation of health deficits in patients with chronic lung diseases is increasingly recognized. There are multiple relationships between aging and ILD on a demographic and a biological level. Frailty conceptualizes the decline of a patient's physiological reserves and complements the chronological and biological aspects of aging. Recent findingsFrailty affects mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The most recent review on pulmonary rehabilitation outcomes [ 52 ] puts emphasis on the potential benefits in improving functional performance and QoL (moderate certainty) and maximum exercise capacity, dyspnoea and long-term survival (low certainty) in ILD patients. In COPD, frail patients respond favourably to pulmonary rehabilitation [ 17 ] and a similar effect could be expected in a population with ILD, although data are still missing for this population [ 53 ]. Because of the high reported prevalence of frailty in patients with ILD [ 50 , 53 ], it is thus crucial to identify and understand the multidimensional concerns of these patients in order to individualise the intervention to suit their needs and priorities [ 54 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The most recent review on pulmonary rehabilitation outcomes [ 52 ] puts emphasis on the potential benefits in improving functional performance and QoL (moderate certainty) and maximum exercise capacity, dyspnoea and long-term survival (low certainty) in ILD patients. In COPD, frail patients respond favourably to pulmonary rehabilitation [ 17 ] and a similar effect could be expected in a population with ILD, although data are still missing for this population [ 53 ]. Because of the high reported prevalence of frailty in patients with ILD [ 50 , 53 ], it is thus crucial to identify and understand the multidimensional concerns of these patients in order to individualise the intervention to suit their needs and priorities [ 54 ].…”
Section: Discussionmentioning
confidence: 96%
“…In COPD, frail patients respond favourably to pulmonary rehabilitation [ 17 ] and a similar effect could be expected in a population with ILD, although data are still missing for this population [ 53 ]. Because of the high reported prevalence of frailty in patients with ILD [ 50 , 53 ], it is thus crucial to identify and understand the multidimensional concerns of these patients in order to individualise the intervention to suit their needs and priorities [ 54 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Preventing deterioration toward frailty is an important goal of ILD care [10 ▪▪ –12 ▪▪ ,14–17 ▪ ]. Central to this is the recognition and management of non-ILD health events and conditions commonly occurring in the general population (Table 1).…”
Section: Processes Of Ageing and The Impact On Interstitial Lung Diseasementioning
confidence: 99%
“…Cohort studies have shown that about half of all patients with ILD have frailty and its importance lies in its predictive role in disability, hospitalisation, and mortality. (37,38) Two models of frailty have been described; Fried's model based on biomedical factors, (39) and the Rockwood's model based with a more holistic definition including psychosocial and environmental factors. (40) Assessment of frailty is important for the possibility of intervention.…”
Section: R8 the Rheumatology Nurse Must Educate The Patient On Infect...mentioning
confidence: 99%